2013
DOI: 10.1364/ao.52.003608
|View full text |Cite
|
Sign up to set email alerts
|

Cascaded diffractive optical elements for improved multiplane image reconstruction

Abstract: Computer-generated phase-only diffractive optical elements in a cascaded setup are designed by one deterministic and one stochastic algorithm for multiplane image formation. It is hypothesized that increasing the number of elements as wavefront modulators in the longitudinal dimension would enlarge the available solution space, thus enabling enhanced image reconstruction. Numerical results show that increasing the number of holograms improves quality at the output. Design principles, computational methods, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
4

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
0
6
0
4
Order By: Relevance
“…A popular approach is to use look-up tables15,22, which is limited to reconstructing simple, low-resolution images. Projection quality can be improved with cascaded diffractive elements31, which is a costly and overly complicated method. While projections of up to several tens of planes have been demonstrated17, it was only for a single dot in each plane and could not be obtained simultaneously, but had to be created sequentially.…”
mentioning
confidence: 99%
“…A popular approach is to use look-up tables15,22, which is limited to reconstructing simple, low-resolution images. Projection quality can be improved with cascaded diffractive elements31, which is a costly and overly complicated method. While projections of up to several tens of planes have been demonstrated17, it was only for a single dot in each plane and could not be obtained simultaneously, but had to be created sequentially.…”
mentioning
confidence: 99%
“…Thus owing to the excellent Bragg selectivity properties of the CGVH, the total SBWP of this system is SBWP = 2.2 × 10 9 . This is 3 orders of magnitude higher than the current state of the art in multiplexed cascaded CGH systems [50], where a system with SBWP = 2.6 × 10 6 was demonstrated. In this case, 2 holograms were encoded in a system of CGHs, each with discreet levels of quantization C = 64, pixel sizes of (∆x = 5 µm, ∆y = 5 µm, ∆z = 0.3 mm) and a hologram size of (L x = 320 µm, L y = 320 µm, L z = 1.5 mm).…”
Section: Dynamic Wave Field Synthesis: Angular Multiplexing and Supermentioning
confidence: 77%
“…This limitation has led to an ever increasing demand of developing 3D holographic optical elements. For instance, stratified CGHs in a cascaded setup have been proposed [49] and it has been shown that by adding more degrees of freedom they expand the system's solution space thus facilitating both angular and frequency multiplexing [50,51]. Another example is presented by thick volume holograms [52].…”
Section: Introductionmentioning
confidence: 99%
“…Liao et al [ 28 ] studied terahertz reconfigurable holographic imaging by mechanical translation of an absorber relative to two fixed discrete dielectric DOEs. Cascaded computer‐generated phase‐only diffractive optical elements for multiplane image formation were simulated by Alkan et al [ 29 ] A lens was utilized in such a cascaded configuration for Fourier transform to project patterns on two imaging planes. In the visible range, Wang et al [ 30 ] demonstrated azimuthal multiplexing with a stratified DOE layout optimized by iterative optimization algorithms.…”
Section: Introductionmentioning
confidence: 99%